Correct Interpretation of Chemical Diagrams Requires Transforming from One Level of Representation to Another - Chittleborough, G.; Treagust, David (Kluwer Academic Publishers, 2008)
Volunteer non-major chemistry students taking an introductory university chemistry course (n = 17) were interviewed about their understanding of a variety of chemical diagrams. All the students’ interviewed appreciated that diagrams of laboratory equipment were useful to show how to set up laboratory equipment. However students’ ability to explain specific diagrams at either the macroscopic or sub-microscopic level varied greatly. The results highlighted the poor level of understanding that some students had even after completing both exercises and experiments using the diagrams. The connection between the diagrams of the macroscopic level (equipment, chemicals), the sub-microscopic level (molecular) and the symbolic level (equations) was not always considered explicitly by students. The results indicate a need for chemical diagrams to be used carefully and more explicitly to ensure learner understanding. Correspondingly, students need to interpret visual chemical diagrams using meta-visualization skills linking the various levels of representation, and appreciating the role of the diagrams in explanations need to be developed.